Factors associated with dental service use of older Korean Americans. Issue 4 (2nd May 2019) - Jang, Yuri; Yoon, Hyunwoo; Rhee, Min‐Kyoung; Park, Nan Sook; Chiriboga, David A.; Kim, Miyong T.
Abstract: Objectives: Based on Andersen's healthcare utilization model, the present study examined factors associated with dental service use in older Korean Americans. Focus was on predisposing characteristics (age, gender, marital status, education and region), oral health needs (problems with teeth or gums and self‐rated oral health) and enabling factors (dental health insurance, length of stay in the United States, acculturation and family network). Methods: Using data from surveys with Korean Americans aged 60 or older (N   =   2128), a Poisson regression model examined predictors of dental visit in the past 12 months. Findings: More than 21% of the sample reported having a problem with teeth or gums, and over half rated their oral health as either fair or poor. Approximately 71% lacked dental health insurance. The number of dental visits in the past 12 months averaged 1.40 (SD = 1.74), with about 38% having no dental visits at all. Multivariate analyses showed that higher levels of education, the presence of a problem with teeth or gums, dental health insurance coverage, longer length of stay in the United States, and larger family networks were associated with 1.01‐1.35 times higher number of dental visits. Conclusion: The findings not only confirmed the critical role of dental health insurance as a service enabler but also highlighted the importance of considering older ethnic immigrants' oral health and dental care from the perspectives of culture and family.